Pola konsumsi atlet sepakbola remaja di Indonesia - Mirza Hapsari Sakti Titis Penggalih; Mohammad Juffrie; Toto Sudargo; Zaenal Muttaqien Sofro (Jurnal Gizi Klinik Indonesia, 2019)
Consumsion pattern of football athlete in IndonesiaBackground: Some early research shows that nutrition in adolescent soccer athlete is still less than the recommended requirements. In Indonesia itself is still lack of studies that describe the pattern of consumption of teenage football athlete.Objective: Describe the consumption pattern in Indonesia teenage football athlete.Method: is study is an observational study at soccer boarding school in Jakarta and Malang. The subjects involved 131 athletes with age 15-19 year. This research conduct on February – May 2016. Researchers examined the intake of food the subject inside the hostel and outside the hostel with 3x24 hour food recall and semi quantitative food frequencies method. Fulfillment nutrient intake of the subject compared with the standard requirements Nutrition Adequacy Score ( AKG 2013) according to age groups.Results: The intake of macro nutrients include energy and carbohydrate was significantly lower than recommendation (p <0.000), whereas protein intake beyond the amount recommended (p <0.000). A total of 33.6% of the subjects taking the supplement with varying types. Types of supplements most consumed supplements vitargo electrolyte (18 people), followed by multivitamins and vitamin C (15 people), calcium (13 people), and herbal supplements (9 people).Conclusion: The consumption pattern teenage soccer athletes for energy and carbohydrate nutrition recommendations do not meet the standards when compared with the needs and AKG 2013. Provision of education needs to be done to improve intake patterns athletes, so the nutritional needs can be met to get the physical quality and the best performance.